6x+1=6(x+1)

Simple and best practice solution for 6x+1=6(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+1=6(x+1) equation:


Simplifying
6x + 1 = 6(x + 1)

Reorder the terms:
1 + 6x = 6(x + 1)

Reorder the terms:
1 + 6x = 6(1 + x)
1 + 6x = (1 * 6 + x * 6)
1 + 6x = (6 + 6x)

Add '-6x' to each side of the equation.
1 + 6x + -6x = 6 + 6x + -6x

Combine like terms: 6x + -6x = 0
1 + 0 = 6 + 6x + -6x
1 = 6 + 6x + -6x

Combine like terms: 6x + -6x = 0
1 = 6 + 0
1 = 6

Solving
1 = 6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| Y=0.15x+0.55 | | 5(15+x)=-70 | | 2*5+8/2=18 | | 2.49+x= | | 9x+1/3x=0 | | 0.20(y-4)+0.16y=0.02y-0.07(60) | | 9x+3x=0 | | (4b+3b^4)-(2b-8b^4)+(5b+9b^2+6b^4)= | | 0.2m=0.3m+2.4 | | 16x^2+32x-65=0 | | m+33=112 | | -12+12=y | | 20-12=2x | | X+5x/3=24 | | 2/3(x-5)=-10+4 | | 3(m-4)+5=5m-21 | | k+37=-2(-1-4k) | | 9(4b-1)=2(9b+30) | | -x=300 | | (t+10.5)+90+2t=180 | | 4(m-4)=2(2m-8) | | 0.15x+0.05(20-x)=0.10(0) | | 26/x=x | | (3X+1)/((9X+3)(3X+7)) | | -20+x=x+23 | | -9=-9+16 | | 7x-35=2x+16 | | 5e^3x=4 | | -6x^2+23x-20=0 | | 8x-7=23-2x | | m-24=53 | | 10-5x=4-3x+7-3x |

Equations solver categories